Tauhid Learning Model Using the Aqidatul Awwam Book to Improve Students’ Morals - Hurril Bariroh (Edumaspul: Jurnal Pendidikan, 2024)
Education tauhid is aspect important in formation morals students, especially at the level of education base. Study This aiming For explore implementation book Aqidatul Awwam in the learning process tauhid as effort increase morals students. Through method study bibliography, research This gather and analyze literature related education tauhid And its implementation in curriculum. Results study show that book Aqidatul awwam No only functioning as a learning medium, however Also as guide in practice values tauhid. Book This contain draft the oneness of Allah, His attributes, as well as principles relevant Islamic creed with formation character student. Strategy implementation covers integration education mark tauhid, strengthening morals, the role of teachers as exemplary, and parental involvement​ in support development morals student. With approach holistic this, it is expected student No only develop in a way academic, but Also own appropriate character​ with Islamic teachings. Study This emphasize importance education tauhid in to form generation of believers, morals noble, and capable face challenges of the modern era.